LEARNING DESIGN DURING THE COVID-19 PANDEMIC IN STAI SUMATERA MEDAN (STUDY ON ADJUSTMENT OF LEARNING OUTCOMES) - Alamsyah Alamsyah; Rahmat Rifai Lubis; Alfiana Utama (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to analyze (1) learning problems during the Covid-19 pandemic, (2) adjusting learning outcomes during the Covid-19 pandemic, (3) measuring the achievement of learning outcomes. This research was conducted at STAI Sumatera Medan. This research uses qualitative research methods, with a descriptive study approach. The results of the study show that the learning problems during the Covid-19 period at STAI Sumatran when viewed specifically in terms of learning outcomes, namely the difficulty of formulating learning objectives due to learning conditions that do not allow maximum in implementing learning, difficulty in formulating goals due to limited access to learning resources, it is difficult to formulate learning objectives due to the lack of enthusiasm and interest of students to take online learning. Enacting policies to adjust learning outcomes according to the conditions and situation of Covid-19, giving students freedom to access learning resources from various references, designing learning strategies that can improve student learning outcomes. As for how to measure achievement by comparing understanding of course material, depth of analysis of course material, student achievement index.Keywords: Learning Design, Learning Outcomes, Covid-19